Concepções docentes sobre o ensino da saúde nos Anos Iniciais - Ferraz de Jesus, Rhenan; Sawitzki, Rosalvo Luis (2019)
This study proposes to analyze health education from the teacher conceptions who work in primary education at a public school. This work is an exploratory and qualitative research of the case study type. For the data collected, we carried out semi structured interviews with five teachers. The results show that: 1) there is a convergence between the school and teachers with the public service of health; 2) it is important to involve schoolchildren to facilitate dialogue regarding the health issue approach in class; 3) the health themes are approached through school projects; and 4) the researched school has seen a unique space for encouraging discussions about health with schoolchildren. In this study, we concluded that the school space aims to raise the awareness of positive attitudes towards the lives of learners.
Objetivou-se analisar as concepções de professoras unidocentes sobre o ensino da saúde nos Anos Iniciais em uma escola pública. Este trabalho trata-se de uma pesquisa qualitativa exploratória e estudo de caso. Para coletar os dados, foram realizadas entrevistas semiestruturadas com cinco professoras. Os resultados apontaram: 1) uma aproximação da escola e professoras com o serviço público de saúde; 2) a importância da participação das crianças em sala de aula para criar diálogos sobre questões relacionadas à saúde; 3) a abordagem de temas em torno da saúde está contemplada em projetos da escola; e 4) a escola é vista como um espaço importante para trabalhar conhecimentos em torno da saúde com as crianças. Conclui-se que, no contexto de estudo, o espaço escolar objetiva à sensibilização de atitudes positivas à vida dos educandos.
Keywords: Teaching; Health; Teacher; Primary education; Ensino^lpt; Saúde; Professor; Ensino Fundamental